2012
DOI: 10.1371/journal.pone.0031084
|View full text |Cite
|
Sign up to set email alerts
|

BACE1 Inhibition Induces a Specific Cerebrospinal Fluid β-Amyloid Pattern That Identifies Drug Effects in the Central Nervous System

Abstract: BACE1 is a key enzyme for amyloid-β (Aβ) production, and an attractive therapeutic target in Alzheimer's disease (AD). Here we report that BACE1 inhibitors have distinct effects on neuronal Aβ metabolism, inducing a unique pattern of secreted Aβ peptides, analyzed in cell media from amyloid precursor protein (APP) transfected cells and in cerebrospinal fluid (CSF) from dogs by immunoprecipitation-mass spectrometry, using several different BACE1 inhibitors. Besides the expected reductions in Aβ1-40 and Aβ1-42, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 54 publications
3
59
0
Order By: Relevance
“…MALDI-TOF/TOFMS measurements were performed using a Bruker Daltonics UltraFleXtreme instrument (Bruker Daltonics, Bremen, Germany) operating in reflector mode, as described previously [21]. …”
Section: Methodsmentioning
confidence: 99%
“…MALDI-TOF/TOFMS measurements were performed using a Bruker Daltonics UltraFleXtreme instrument (Bruker Daltonics, Bremen, Germany) operating in reflector mode, as described previously [21]. …”
Section: Methodsmentioning
confidence: 99%
“…This was supported, when using potent BACE-1 inhibitors in vitro and in vivo (Asai et al, 2006; Nishitomi et al, 2006; Hussain et al, 2007; Stanton et al, 2007; Sankaranarayanan et al, 2008). Interestingly, some studies showed that by inhibition of Aβ1-x generating β-secretase activity, alternative N-terminally truncated Aβ peptides increase (Haass et al, 1995; Schrader-Fischer and Paganetti, 1996; Takeda et al, 2004; Schieb et al, 2010; Mattsson et al, 2012). Analysis of Aβ species in BACE-1 knock-out mice likewise revealed that the generation of Aβ1-x peptides was completely abolished while N-terminally truncated Aβ variants could still be generated (Nishitomi et al, 2006).…”
Section: Conventional App Processingmentioning
confidence: 99%
“…One of the truly longitudinal studies of cognitively normal individuals with repeated CSF samples suggests that Ab42 and tau changes occur in parallel and predict upcoming cognitive symptoms better than absolute baseline levels [101]. CSF measurements may track trajectories of specific Ab and APP metabolites [104][105][106][107], and downstream effects on secondary phenomena, such as reduced axonal degeneration in response to a disease-modifying drug as measured by CSF tau levels [108,109].…”
Section: Longitudinal Changes In Csf Ad Biomarkers and Usage In Clinimentioning
confidence: 99%